2020
DOI: 10.1002/saj2.20077
|View full text |Cite
|
Sign up to set email alerts
|

Stand ages adjust fluctuating patterns of soil respiration and decrease temperature sensitivity after revegetation

Abstract: Revegetation plays an essential role in controlling soil erosion and influencing soil respiration (Rs) by changing the vegetation coverage and soil biochemical characteristics. Soil respiration and its temperature sensitivity (Q10) have been studied comprehensively. However, the effect of stand age after revegetation on Rs and Q10 remains unclear. We selected four stands (i.e., eroded hillslopes [EBs] and 0‐ to 5‐yr, 5‐ to 10‐yr, and 10‐yr apple orchards) to investigate the changes in Rs and Q10 values. A soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…Many studies believed that soil temperature were the main factors affecting soil respiration. It can explain seasonal changes in soil respiration [39,40]. In this study, the soil respiration and soil temperature of four reconstructed soils was exponentially correlated, which was consistent with the research conclusions of most scholars [41,42].…”
Section: The Relationship Between Soil Respiration and Hydrothermal Factorssupporting
confidence: 89%
“…Many studies believed that soil temperature were the main factors affecting soil respiration. It can explain seasonal changes in soil respiration [39,40]. In this study, the soil respiration and soil temperature of four reconstructed soils was exponentially correlated, which was consistent with the research conclusions of most scholars [41,42].…”
Section: The Relationship Between Soil Respiration and Hydrothermal Factorssupporting
confidence: 89%
“…The temperature sensitivity of R S (defined as Q 10 ) was always applied to represent the response of R S to temperature change (Meyer et al ., 2018). R S and Q 10 are influenced by multiple factors (e.g., vegetation coverage, the ages of plants, soil temperature, soil moisture, soil physicochemical and microbial properties), which can be altered by land‐use change (Kreba et al ., 2013; Camara Ferreira et al ., 2016; Wang et al ., 2016; Wang et al ., 2018; Tong et al ., 2020). More specific, R S is positively associated with root biomass amount, and varied with crop types and the stand years under different land‐use types, because of the different allocation of photosynthetic products (Wang et al ., 2016; Yao et al ., 2019; Tong et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…R S and Q 10 are influenced by multiple factors (e.g., vegetation coverage, the ages of plants, soil temperature, soil moisture, soil physicochemical and microbial properties), which can be altered by land‐use change (Kreba et al ., 2013; Camara Ferreira et al ., 2016; Wang et al ., 2016; Wang et al ., 2018; Tong et al ., 2020). More specific, R S is positively associated with root biomass amount, and varied with crop types and the stand years under different land‐use types, because of the different allocation of photosynthetic products (Wang et al ., 2016; Yao et al ., 2019; Tong et al ., 2020). Furthermore, the different quality and quantity of substrate, soil carbon degrading enzymes secreted by microbes and the microbial community structure can also result in the shifted R S and Q 10 (Fang et al ., 2014; Camara Ferreira et al ., 2016; Zhang et al ., 2016b; Wang et al ., 2018; Zhang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although water content and temperature have been established to be the main environmental factors influencing soil respiration in Chinese farmland ecosystems, this respiration and its components are characterized by differential responses to variations in temperature and water content 30 . The findings of numerous studies have indicated that soil temperature is the main factor influencing soil respiration, which is clearly reflected in the observed seasonal changes 31 , 32 . Consistent with the opinion of a majority of scholars 33 , 34 , we detected an exponential correlation between soil respiration and soil temperature among the four assessed reconstructed soils.…”
Section: Discussionmentioning
confidence: 99%